2015
DOI: 10.1590/1808-1657000552013
|View full text |Cite
|
Sign up to set email alerts
|

Espécies de Anastrepha (Diptera: Tephritidae) em pomares de goiaba: diversidade, flutuação populacional e fenologia do hospedeiro

Abstract: RESUMO:Os estudos foram conduzidos em pomares de goiaba, em dois municípios do estado de Sáo Paulo. Em Monte Alegre do Sul, o levantamento foi realizado em uma estação experimental da Agência Paulista de Tecnologia dos Agronegócios, na qual foram cole tadas 13 espécies de Anastrepha, desde janeiro de 2002 a dezembro de 2003. Em Monte Alto, em pomar comercial, foram coletadas oito espécies, desde janeiro a dezembro de 2004. Anastrepha fraterculus foi a espécie mais frequente nos dois municípios. Os parâmetros c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
4
0
2
Order By: Relevance
“…Most research on tephritoids focuses on the economic importance of several species associated with agriculture (Lemos et al 2015), whereas studies in native areas (Uramoto et al 2008;Uchoa & Nicácio 2010) are scarce. Protected natural areas, such as conservation units, represent one of the best strategies to conserve local biodiversity.…”
Section: Introductionmentioning
confidence: 99%
“…Most research on tephritoids focuses on the economic importance of several species associated with agriculture (Lemos et al 2015), whereas studies in native areas (Uramoto et al 2008;Uchoa & Nicácio 2010) are scarce. Protected natural areas, such as conservation units, represent one of the best strategies to conserve local biodiversity.…”
Section: Introductionmentioning
confidence: 99%
“…Jesus- Barros et al (2012), in a study carried out in the state of Amapá, observed that the highest rates of infestation by Anastrepha were recorded in native fruits of the Amazon region. Lemos et al (2015), in a study carried out in the southeast region of Brazil, found that the population dynamics of Anastrepha in guava orchards was influenced by the availability of alternative hosts in the areas adjacent to the orchard.…”
mentioning
confidence: 99%
“…Sixteen species of Anastrepha and ten species of Neosilba have been previously associated with guava fruits in Brazil, and the importance of each of these species as pests of guava fruits varies depending on the region where the guava grows (Araujo et al 2013, Lemos et al 2015b, Raga et al 2015, Pinto 2017, Sousa et al 2021, Zucchi & Moraes 2022a. The diversity and abundance of fruit fly species in orchards is influenced by climate, altitude, hosts and adjacent orchards (Silva et al 2010).…”
Section: Introductionmentioning
confidence: 99%